Cleaner production as a preventive environmental strategy in the cocoa paste production process. A case in the Ecuadorian Amazon - Molina-Cedeño, Carla Stephany (2020)
Cocoa is one of the most important crops in Ecuador, destined for export to be used in making chocolate in other countries. The objective of this work was to analyze the environmental performance and the potentialities of applying cleaner production mechanisms (CP) in the Association of producers of fine aroma cocoa "Tsatsayaku". The CP tools used were the initial environmental review, ecomaps, and process analysis. The results show that mucilage and cocoa husk generation are the main environmental problems of the process. Two improvement options were proposed and evaluated to control and reduce process contamination. The analysis shows a B / C ratio of 1.38 and the Net Present Value is $ 36,001.37 with an Internal Rate of Return of 249.29%. Finally, the application of practices and technologies framed in CP systems can optimize the use of raw materials and reduce the solid and liquid contaminants generated.